Dilemas da democracia brasileira : um estudo da representação política institucional do município de Nova Mutum (2000 a 2020) - Pedroso, Loreni Aparecida (2023)
The study of democracy has been a recurring theme among researchers since Classical Antiquity, and in the first two decades of the 21st century, it has raised concerns about its effectiveness. Significant changes in the political landscape and popular participation have prompted in-depth analyses. Scholars like Manuel Castells (2018), Robert Dahl (2012), and Santos (2016) have questioned the representativeness of democracy, indicating a crisis in representative democracy. Against this backdrop, this research aims to analyze institutional political representation in Nova Mutum, Mato Grosso, from 2000 to 2020, focusing on the executive and legislative branches. The chosen municipality stands out for its history and economic importance, particularly in agricultural product exports, founded in the same year as Brazil's redemocratization. To achieve the objective and build an understanding of the problem, the research will adopt a documentary, bibliographic approach with qualitative techniques, utilizing data from the TSE platform and IBGE. The selection of this theme is associated with the field of political sociology, gaining significance for shedding light on contemporary debates and local political data contributing to the understanding of the state's political development. The findings suggest a dominant political group in local politics that has remained in municipal public administration throughout the analyzed period.